Rancang Bangun Aplikasi Peramalan Permintaan Barang Dengan Metode Pemulusan Eksponensial Winter Pada PT. Supramedika Prima - Putra, Ridho Denanda; Tjandrarini, A.B.; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: PT. Supramedika Prima Perwakilan Surabaya is a sole importer of medical devices and reagents from different brands in Indonesia. It’s customers are clinical laboratory and hospital in all region inside the east half of Indonesia. As a sole importer, this company must have a sufficient amount of inventory in order to complete each of their customer’s needs. In the mean time, the sale manager of this company is having a difficulty in estimating the amount of goods needed to be sold in the upcoming period. This issue needs to be resolved in order to prevent any customers that would stop buying goods from the company. An application to provide a forecast of goods demand in the future is needed to solve the issue. According to the data pattern test, the sales data has a close similarity to the seasonal and trend data pattern. That data pattern is best solved by using a specific method for forecasting, the Winter Exponential Smoothing method. After tested, the application could produce an average error from the results of forecasting at 13,2%, while the success level of implementing the Winter method is at 85,7%.